Sierra Leone : Fifth Review Under the Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance of Performance Criterion, Request for Modification of Performance Criteria, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Fifth Review Under the Poverty Reduction and Growth Facility Arrangement for Sierra Leone. Program performance in the first half of 2009 was satisfactory. All end-June quantitative performance criteria were met, as were all end-June structural benchmarks, although one with a delay. One of the two structural benchmarks for September 2009 was met, while the other was missed. Fiscal policy for the remainder of 2009 will aim to keep domestic revenue collection on track while containing unanticipated spending pressures.